Habitat characteristics of Asian moon scallops (Amusium pleuronectes) in Makassar Strait and Bone Bay Waters, Indonesia - BUDIYATI BUDIYATI; SHARIFUDDIN BIN ANDY OMAR; ANDI NIARTININGSIH; ITA WIDOWATI; NUDIN KASIM; MUHAMMAD YUSUF; ANDI DYNA RIANA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Budiyati, Omar SBA, Nartiningsih A, Widowati I, Kasim N, Yusuf M, Riana AD. 2024. Habitat characteristics of Asian moon scallops (Amusium pleuronectes) in Makassar Strait and Bone Bay Waters, Indonesia. Biodiversitas 25: 3423-3430. Scallops (Amusium pleuronectes Linnaeus 1758), also known as axe clam, is a type of bivalve mollusk from the family Pectinidae that lives in marine or generally in coastal areas and can be found in all marine waters, including tropical regions such as Indonesia. Scallops are of economic value as a food source because scallops contain a lot of protein and are low in fat. In South Sulawesi, Indonesia, scallops are found in almost all coastal areas, both on the coast of the Makassar Strait and on the coast of Bone Bay and Flores Sea waters. The present study aims to illustrate and compare the habitat characteristics of the Asian moon scallops (A. pleuronectes) from Makassar Strait and Bone Bay. The research method used is quantitative descriptive, with the type of research conducted being a comparative study. The method and type of research used are based on the purpose of the study, which is to compare the habitat characteristics of scallops that live in the waters of the Makassar Strait, which is in the western side of South Sulawesi (Sulawesi Island), and Bone Bay which is in the eastern side of South Sulawesi (Sulawesi Island). The study was conducted from January to October 2022 in two water areas, Makassar Strait in Makassar City and Bone Bay in Bone District. The data consisted of primary data obtained in the research fields by measuring physical parameters, including temperature, salinity, water depth, DO, and pH. The study results show that the temperature in the two sites was around 28.0-30.5oC, salinity around 28.0-39.0 ppt, the water's depth around 9-20 m, DO about 5.0-6.0 ppm, and pH around 5.60-8.75. In conclusion, the habitat of the Asian moon scallops in Makassar Strait dan Bone Bay has relatively similar characteristics.